From ethnomathematics to school geometry: Developing an iceberg-based learning trajectory through the Raja Rokan palace - Nurrahmawati; Lusi Eka Afri; Arcat (CV. FOUNDAE, 2026)
Background: Ethnomathematics has emerged as an effective approach for connecting cultural heritage with school mathematics. Nevertheless, most existing studies focus primarily on identifying mathematical ideas embedded in cultural artefacts without transforming them into systematic instructional designs that support classroom learning. Aims: This study aimed to develop an Iceberg-based Learning Trajectory (ILT) that translates ethnomathematical concepts embedded in the Raja Rokan Palace into meaningful geometry learning for junior high school students and to design a prototype student worksheet aligned with the proposed trajectory. Method: A qualitative educational design approach grounded in ethnomathematics was employed. Data were collected through observations, documentation, and previous ethnomathematical findings. The identified mathematical concepts were analysed using content analysis and mapped onto the four levels of the Iceberg Model to construct an ILT comprising learning objectives, learning activities, anticipated students’ thinking, instructional scaffolding, and worksheet design. Results: The findings identified four geometric concepts rectangles, triangles, trapezoids, and semicircles which were systematically transformed into an ILT that supports students’ progressive transition from contextual cultural experiences to formal geometric reasoning. The study also produced a culturally responsive worksheet prototype and instructional design principles for developing Iceberg-based learning trajectories. Conclusion: The proposed ILT provides a transferable framework for integrating cultural heritage into geometry learning and contributes to the advancement of culturally responsive mathematics education. Future studies should examine its classroom implementation and effectiveness.